Literature Review: Konseling Keluarga terhadap Kekerasasan dalam Rumah Tangga (KDRT) - Bachtiar Safrudin; Kartika Setia Purdani; Rizka Dwi Purnamasari; Putri Nadila; Siti Khadijah; Virna Nur Halizza; Nasua Arya Putri; Adam Rizki Azzahdi; Arrasyidi Alfatahillah (El-Mujtama: Jurnal Pengabdian Masyarakat, 2026)
Family counseling has an important role in preventing and addressing domestic violence (DV), which remains a major social issue with significant psychological, physical, and intergenerational impacts. This study aims to analyze various research findings related to the effectiveness of family counseling in reducing the incidence of DV in Indonesia. Using a literature review method, articles published between 2021–2025 were systematically selected from databases such as Google Scholar, Garuda, and other online sources using keywords including family counseling, domestic violence, and abuse. The reviewed studies show that family counseling improves communication patterns, enhances empathy, increases self-awareness, and helps both victims and perpetrators build healthier relationship dynamics. Counseling interventions also contribute to reducing psychological symptoms experienced by victims, including fear, anxiety, and trauma, while helping perpetrators recognize and manage aggressive behaviors. In addition, several studies highlight that counseling plays a preventive role by strengthening family resilience and breaking intergenerational cycles of violence. Overall, family counseling demonstrates strong potential as a curative and preventive strategy in decreasing DV cases in Indonesia. Strengthening access, reducing stigma, and increasing multidisciplinary support are crucial to maximizing the effectiveness of family-based interventions.